Teaching Health versus Treating Illness: The Efficacy of Three Principles Correctional Counseling with People in an English Prison. (July 2018) - Kelley, Thomas M.; Hollows, Jacqueline; Lambert, Eric G.; Savard, Dennis M.; Pransky, Jack
Three principles correctional counseling (3PCC) posits that people in prison have inner mental health they have obscured to varying degrees with their own thinking. 3PCC further posits that people in prison can rekindle and sustain this inner health via understanding how three psychospiritual principles—Universal Mind, consciousness, and thought—coalesce to form people's psychological experience. We review the three principles and explain how exposure to these principles can lead to improved mental health and improved behavior. Then, we describe 3PCC and distinguish it from prevailing correctional counseling methods. Finally, we present a preliminary study that examines the efficacy of 3PCC for improving the mental health and behavior of people in an English prison. Our findings show that participants exposed to 3PCC showed a significant improvement in mental well-being and purpose in life, significant reductions in anxiety and anger, and improved behavior in the prison community.